Persistent active avoidance correlates with activity in prelimbic cortex and ventral striatum - Bravo-Rivera, Christian; Roman-Ortiz, Ciorana; Montesinos-Cartagena, Marlian; Quirk, Gregory J. (Frontiers in Behavioral Neuroscience, 2015)
Excessive avoidance is a prominent symptom of anxiety disorders and is often resistant to extinction-based therapies. Little is known about the circuitry mediating persistent avoidance. Using a recently described platform-mediated active avoidance task, we assessed activity in several structures with c-Fos immuno-labeling. In Task 1, rats were conditioned to avoid a tone-signaled shock by moving to a safe platform, and then were extinguished over two days. One day later, failure to retrieve extinction correlated with increased activity in the prelimbic prefrontal cortex (PL), ventral striatum (VS), and basal amygdala (BA), and decreased activity in infralimbic prefrontal cortex (IL), consistent with pharmacological inactivation studies. In Task 2, the platform was removed during extinction training and fear (suppression of bar pressing) was extinguished to criterion over 3-5 days. The platform was then returned in a post-extinction test. Under these conditions, avoidance levels were equivalent to Experiment 1 and correlated with increased activity in PL and VS, but there was no correlation with activity in IL or BA. Thus, persistent avoidance occurs independently of deficits in fear extinction and its associated structures.